Indigenous Maya-Mam leadership competencies: a grounded theory study - Lamino, Pablo; Boren-Alpízar, Amy E.; Headrick, Jason; Burris, Scott; Carpio, Carlos (Frontiers in Sociology, 2025)
IntroductionThis study explores the leadership competencies within the Indigenous Maya-Mam community, aiming to understand the specific skills and qualities exhibited by Maya-Mam leaders. The research seeks to address the gap in literature regarding Indigenous leadership practices, particularly focusing on how cultural values influence leadership behaviors.MethodsQualitative methods were employed for this study, including interviews and thematic analysis. Data collection took place in various Maya-Mam communities in Guatemala, where participants were selected based on their roles and experiences within the community leadership structures.ResultsThe study identified several key competencies among Maya-Mam leaders, including leading by example, promoting inclusive leadership, valuing bilingual proficiency, and emphasizing community solidarity. These competencies underscored the leaders’ roles as both inspirations and facilitators of community development.DiscussionThe findings suggest that Maya-Mam leadership is deeply rooted in cultural values and community dynamics, influencing how leaders engage with their roles and responsibilities. This aligns with broader research on Indigenous leadership, highlighting similarities and unique aspects of Maya-Mam leadership practices. The study underscores the importance of understanding local contexts and cultural values in leadership development initiatives within Indigenous communities. Future research could further explore comparative studies across different Indigenous groups to enhance understanding and inform effective leadership strategies.